A review of the problematic adhesion prophylaxis in gynaecological surgery - Hirschelmann, Anja; Wallwiener, Markus (Archives of gynecology and obstetrics, 2012)
Background: Adhesions lead to considerable patient morbidity and are a mounting burden on surgeons and the health care system alike. Although adhesion formation is the most frequent complication in abdominal and pelvic surgery, many surgeons are still not aware of the extent of the problem. To provide the best care for their patients, surgeons should consistently inform themselves of anti-adhesion strategies and include these methods in their daily routine. Methods: Searches were conducted in PubMed and The Cochrane Library to identify relevant literature.FindingsVarious complications are associated with adhesion formation, including small bowel obstruction, infertility and chronic pelvic pain. Increasingly, an understanding of adhesion formation as a complex process influenced by many different factors has led to various conceivable anti-adhesion strategies. At present, a number of different anti-adhesion agents are available. Although some agents have proved effective in reducing adhesion formation in randomised controlled trials, none of them can completely prevent adhesion formation. Conclusion: To fulfil our duty to provide best possible care for our patients, it is now time to regard adhesions as the most common complication in surgery. Further research is needed to fully understand adhesion formation and to develop new strategies for adhesion prevention. Large clinical efficacy trials of anti-adhesion agents will make it easier for surgeons to decide which agent to use in daily routine.
Published online: 30 October 2011
Gesehen am 12.07.2018